Empowering Smart Factories: The Role of Cyber-Physical Systems in Revolutionizing Autonomous Manufacturing - Adhikari, Vineeta; Andola, Deep Chandra; Singh, Harendra Pratap (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The integration of Cyber-Physical Systems (CPS) in manufacturing is revolutionizing the transition to smart factories, enabling real-time monitoring, intelligent decision-making, and autonomous operations. CPS bridges physical processes with digital technologies, leveraging sensors, IoT, and AI to enhance efficiency, flexibility, and sustainability. This paper explores the architecture, functionalities, and transformative impact of CPS on autonomous manufacturing, highlighting innovations like predictive maintenance, mass customization, and resource optimization. Despite challenges such as cybersecurity and cost barriers, CPS holds immense potential to reshape manufacturing by fostering resilience and agility. Future advancements in connectivity and AI promise further breakthroughs in this domain.